OFR-61(5)-78 Coal Mine Electrical System Evaluation - Volume V - Battery And Battery-Charging Safety - Lloyd A. Morley (The National Institute for Occupational Safety and Health (NIOSH), 1977)
The primary goal of this research report is to discuss safety considerations involved in the use of lead-acid batteries for traction purposes in underground coal mines. In order to arrive at the objective, the topic of battery safety has been divided into two specific areas. The first deals with the fact that batteries emit hydrogen gas during and after the charge cycle. Hydrogen gas can be the source of dangerous explosions or mine fires. The second major topic deals with the electrical nature of the battery and battery-charging systems, which also provides a source of mine fires as well as electrocution hazards. In addition to the discussion on battery safety, a literature review has been undertaken to acquaint the reader with some basic concepts inherent to the battery usage process. The result of this research is a set of design specifications and procedural recommendations directed at improving the safety factors inherent in any underground battery usage scheme.